Mapping the pattern and trends of extrapulmonary tuberculosis - S Rama Prakasha; G Suresh; Ivor Peter D′sa; Shobha S Shetty; S Ganesh Kumar (Journal of Global Infectious Diseases, 2013)
Background and Objectives: There has been a rapid expansion of the directly observed treatment short-term (DOTS) under the revised national tuberculosis control program throughout India in the last decade. Few reports exist detailing individual DOTS centers′ experiences with regard to extrapulmonary tuberculosis (EPTB) in a medical college hospital setting. Materials and Methods: This is a retrospective, record-based study of patients with the diagnosis of EPTB, in all age groups. Data on all consecutive EPTB cases diagnosed at the K. S. Hegde Medical College and Hospital, Deralakatte, Mangalore from 1 January 2005 to 31 December 2011 at the DOTS centre attached to this hospital were collected, analyzed by Mantel-Haenszel Chi square for linear trend and described in proportion or percentages. Results: Among 1267 cases registered for treatment of all forms of tuberculosis, 528 (41.67%) had EPTB. Around half of the cases of EPTB (269, 51%) were among adult age groups and the majority of cases (342, 64.77%) received Category-I treatment. Pleural TB was the commonest type of EPTB (n = 148, 28.03%), followed by lymph node TB (n = 131, 24.81%). Involvement of lymph nodes was the commonest manifestation among the less than 14 years′ age group (27, 58.7%), while involvement of pleura was more common among > 65 years′ age group (23, 45.1%). The difference in the occurrence of EPTB by site between males and females is statistically significant with a P value of <0.005. There is a significant increase in the number of cases of tuberculosis affecting bones and joints, and other forms of tuberculosis over the years. Conclusion: The burden of EPTB is more among the productive age group. Increase in the trend of bone and joint tuberculosis, and other rare forms of EPTB is a point of concern highlighting the importance of strengthening the services towards this group.